Characteristics of fishers: a case study of Zeekoevlei, Cape Town - Gilliland, Toshca-Lee (Department of Environmental and Geographical Science, 2017)
Fisheries are complex socio-ecological systems consisting of both human and ecological components. Managing fishery resources has almost always focused on ecological concerns without due consideration being given to the human dimensions. However, increasingly more scholars are recognising the need to integrate the human dimensions of fisheries management with the ecological concerns. Managing a fishery solely on the basis of ecological information will result in the management strategies being unsuccessful. Understanding the human dimensions is important as it provides insights into who participates in the fisheries industry, and what the behavioural patterns and motivations of the fishers are. This study focused on understanding the human dimensions of fishing at Zeekoevlei, focusing on who the fishers are and why they engage in fishing. It also addressed the source of conflicts at Zeekoevlei. The management of Zeekoevlei and fishing activities is also considered. A mixed methods approach, using a case study design, was adopted. The sample included fourteen fishers and six individuals involved on various levels of management of Zeekoevlei. Data-collection methods included the use of a structured questionnaire and semi-structured interviews. On the basis of this study, the demographics show that two types of fishers were found at Zeekoevlei – recreational and small scale. These fisher groups display contrasting socio-demographic profiles; however, a correlation between socio-demographics and motivations was observed. Recreational fishers appear to be white, educated males who are employed and engage in fishing for a sense of achievement, which is underpinned by the size of the fish. Small-scale fishers, on the other hand, are unemployed coloured males, with low levels of education and to this group of fishers the Zeekoevlei fishery system has an important function as it is used to diversify livelihoods. As with many fisheries, conflicts are prevalent at Zeekoevlei. These conflicts arise between fishers because Zeekoevlei has limited demarcated fishing spots and fishers display ownership over these spots; to exacerbate this situation, Zeekoevlei is located in an open reserve, which makes it easier for fishers to enter the reserve illegally. The management of the vlei appears to be based on recreational considerations with unclear measures to accommodate small-scale fisheries.